Enhancing educational equity and sustainability: a fuzzy-based framework for optimal school site selection - Yifei Meng; Ruidun Chen; Xiao Huang; Yanhong Liu; Cong Fu; Yan Liu; Yuchen Li; Yanqing Xu (International Journal of Digital Earth)
Educational equity is a crucial component of social fairness, essential for a harmonious society. This study employs Multi-Criteria Decision Analysis (MCDA), integrating Geographic Information Systems (GIS) and the Fuzzy Analytic Hierarchy Process (FAHP), to assess and improve the distribution of middle school resources in Henan Province, China. We applied fuzzy techniques simultaneously in the weighting and classification processes of school site selection criteria. We evaluated economic, transportation, social, and safety factors and incorporated educational resource allocation and teaching environment factors into the site selection criteria. Our study finds that over 39% of land in Henan Province is unsuitable for school construction. We also identified areas on the urban periphery and in the eastern and southern regions, which have convenient transportation and high educational demand, as potential sites for middle schools. Sensitivity analysis further validates the reasonableness of the expanded decision criteria. Our approach addresses the limitations of traditional AHP in handling fuzzy information, considers long-term resource allocation and ecological development of school operations, and provides planners with a robust framework for making scientifically informed site selection decisions, thereby promoting educational equity and sustainable development.